Realising the artificial chemical cell with vesicles - Pasparakis, George (2009)
Responsive biomedical materials span a plethora of applications in the biomedical field, from stents, hydrogels, degradable implants to drug delivery systems, and are in constant further development to give properties that ultimately improve the quality of life and prevent disease. In an effort to develop cell-interacting constructs we sought to synthesize polymers with bioresponsive and even “life-like” properties. By exploiting living polymerization techniques we aim to build self-assembled capsule-mimicking structures (i.e. vesicles) that can serve as prototype copycats of natural cell membranes. Also, we aim to establish a primitive communication platform of the artificial structures with their natural counterparts (i.e. bacterial cells) by using the “glyco-code” as a means of biochemical language. First, model thermoresponsive polymers are utilized that bear carbohydrate moieties to study polymer-cell interactions via multivalency and ligand-receptor interactions. The glycopolymers were found to induce bacterial aggregation of a specific bacterial strain through specific molecular recognition effects. In chapter three, block-copolymer vesicles are synthesized that comprise sugar groups on their coronae and also interact with bacteria through multiple specific ligand-receptor interactions. Also, molecular transport of a model dye from the vesicles to the bacterial cells is facilitated by discrete vesicle-bacteria complex formation. Chapter four explores the communication networks employed by bacterial cells, that is quorum sensing, and simple polymers are tested as molecular quorum quenchers that modulate the quorum sensing response of bacteria through autoinducers scavenging. Ultimately, we seek for an integrated platform to set up an “imitation game” where artificial entities, such as the polymer vesicles, can act as prototype cell-mimics that can actively intervene to the bacterial communication networks. Aspects of the principles and practical requirements to prove the concept are discussed in the final chapter.